Influence of rabeprazole and famotidine on pharmacodynamic profile of dual antiplatelet therapy in clopidogrel-sensitive patients: The randomized, prospective, PROTECT trial. (2nd April 2020) - Ahn, Jong-Hwa; Park, Yongwhi; Bae, Jae Seok; Jang, Jeong Yoon; Kim, Kye-Hwan; Kang, Min Gyu; Koh, Jin-Sin; Park, Jeong Rang; Hwang, Seok-Jae; Kwak, Choong Hwan; Hwang, Jin-Yong; Jeong, Young-Hoon
Abstract: Although acid suppressants are needed to attenuate gastrointestinal bleeding (GIB) after percutaneous coronary intervention (PCI), pharmacodynamic interaction between clopidogrel and proton pump inhibitor (PPI) can increase the risk of high platelet reactivity (HPR). We sought to evaluate serial changes of platelet measures and influence of rabeprazole on platelet measures. After 600-mg clopidogrel loading for elective PCI, clopidogrel-sensitive patients were recruited and randomly assigned to add rabeprazole of daily 20 mg (n = 40) or famotidine of daily 40 mg (n = 40). Platelet measures were performed with light transmittance aggregometry and VASP-P assay. Primary endpoint was 5 μM ADP-induced platelet aggregation (PA) at 30-day follow-up. HPR was defined as 5 μM ADP-induced PA > 46%. Baseline platelet measures did not differ significantly between the groups. The 30-day level of 5 μM ADP-induced PA was similar between the famotidine vs. rabeprazole group (30.0 ± 16.4% vs. 30.2 ± 13.9%, P = .956). In addition, other platelet measures were comparable between the groups. At 30-day follow-up, the incidence of HPR was similar between the famotidine and rabeprazole groups (20.5% vs. 15.4%; P = .555). In conclusion, adjunctive use of rabeprazole showed the similar antiplatelet effect even in clopidogrel-sensitive patients compared with adjunctive famotidine, which may support the similar effect of rabeprazole and famotidine on the antiplatelet effect of dual antiplatelet therapy with clopidogrel plus aspirin.